PENGARUH PEMBERIAN MAKANAN JAJANAN, PENDIDIKAN GIZI, DAN SUPLEMENTASI BESI TERHADAP STATUS GIZI, PENGETAHUAN GIZI, DAN STATUS ANEMIA PADA SISWA SEKOLAH DASAR - Adhitya Aji Candra; Budi Setiawan; Rizal Damanik (Jurnal Gizi dan Pangan, 2013)
The objective of this research were to analyze the effect of snack feeding, nutrition education, and iron supplementation to nutritional status, nutrition knowledge, and anemia status in elementary school students. The study was conducted in SDN Palasari 02 Kecamatan Cijeruk, Kabupaten Bogor, Jawa Barat. The design of this study was pre-post intervention study. The number of subjects were 81 students. The result showed that snacking did not give significant improvement on nutritional status (p>0.05). Nutrition education was significant in improving nutrition knowledge (p<0.05), while iron supplementation intake gave a significant improvement on anemia status (p<0.05).Keywords: